FDI, financial development and economic growth: evidence of causality from East and South East Asian countries. (1st January 2014) - Samad, Abdus; Akhtaruzzaman, Muhammad
This paper empirically investigates causal relationship – short run and long run – among foreign direct investment (FDI), financial development, and economic growth in ten East and South East Asian countries using vector error correction model (VECM) and VEC Granger causality/Wald Exogeniety tests. The paper finds that in Singapore, Malaysia and China, GDP growth Granger causes FDI. On the other hand, financial market development (FMD) Granger causes FDI in Singapore, Malaysia, and Sri Lanka. Bidirectional Granger causality between GDP and FDI is observed in Indonesia and India. FDI does not Granger cause economic growth (GDP) in all ten countries under study during 1980–2010. It suggests that FDI follows either economic growth or financial market development in these countries.